A level of special kinetic abilities of amateur wrestlers - Petija, A. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2016)
The goal of this study was to find actual level of special kinetic abilities of amateur wrestlers. We tested 6 amateur free style wrestlers in men category. We found, that the highest level of special kinetic abilities of wrestlers within test, in comparison to top-wrestlers, had wrestlers in a 4m hands climbing test, which we evaluated dynamical strength of upper limbs. In comparison with the results of top-wrestlers in a senior category, publicized in the study of Curby (2010), wrestlers achieved worse average rates than 0, 34 seconds. In other tests special dexterity, 10 throws of dummy with layback and a dumbbell row in a lying position to a breast our amateur wrestlers achieved worse values than top-wrestlers. The lowest level of values had our sportsmen in the test dumbbell row in a lying position to a breast in which in comparison with a study of Stefanovsky (2015), level of values is worse than 43, 62 % in comparison to junior and senior wrestlers in SR (n=10).